The Road to a Trustworthy 6G; On the Need for a “Zero Trust 6G” Paradigm - Køien, Geir M. (Journal of Mobile Multimedia, 2024)
The high-level aspects of 6G are slowly being agreed upon. It is safe to assume that 6G will bring many enhancements to 5G, including pervasive application of Artificial Intelligence (AI) and Machine Learning (ML) services. The “softwareization” trend is likely to continue and become even more prevalent. Security and trustworthiness are recognized goals for 6G. Accordingly, we predict that Zero Trust principles will become fully integrated in the 6G architecture. While necessary, this will not be sufficient. With the “softwareization” in mind, we postulate a need for increased focus on software development and deployment practices. Thus, we propose to extend the Zero Trust paradigm to encompass software development assurance and bring about a Zero Trust 6G regime. This will also be in line with the current developments for improved accountability for software and services.